Metabolic Reprogramming of Vascular Endothelial Cells: Basic Research and Clinical Applications - Peng, Hanlin; Wang, Xiuli; Du, Junbao; Cui, Qinghua; Huang, Yaqian; Jin, Hongfang (Frontiers in Cell and Developmental Biology, 2021)
Vascular endothelial cells (VECs) build a barrier separating the blood from the vascular wall. The vascular endothelium is the largest endocrine organ, and is well-known for its crucial role in the regulation of vascular function. The initial response to endothelial cell injury can lead to the activation of VECs. However, excessive activation leads to metabolic pathway disruption, VEC dysfunction, and angiogenesis. The pathways related to VEC metabolic reprogramming recently have been considered as key modulators of VEC function in processes such as angiogenesis, inflammation, and barrier maintenance. In this review, we focus on the changes of VEC metabolism under physiological and pathophysiological conditions.